2012
DOI: 10.1177/0162353212451735
|View full text |Cite
|
Sign up to set email alerts
|

Self-Esteem and Self-Concept Examination Among Gifted Students With ADHD

Abstract: Intellectually gifted students with attention-deficit/hyperactivity disorder (ADHD) face unique academic and social challenges, yet little research has been conducted with this population. The purpose of this study was to examine the self-esteem and self-concept of intellectually gifted children with and without a coexisting diagnosis of ADHD. Data were gathered from 112 children, aged 6 to 18, identified as having high cognitive ability (IQ of 120, 91st percentile, or above); 54 participants also met diagnost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
9

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 48 publications
1
43
0
9
Order By: Relevance
“…They face risks similar to those of their nongifted counterparts, including school performance, social functioning, and mental health concerns (Antshel et al, , ). Gifted children with ADHD are more likely than gifted children without ADHD to indicate overall self‐esteem difficulties and lower levels of happiness and behavioral satisfaction (Foley‐Nicpon, Rickels, Assouline, & Richards, ).…”
Section: Key Conceptsmentioning
confidence: 99%
“…They face risks similar to those of their nongifted counterparts, including school performance, social functioning, and mental health concerns (Antshel et al, , ). Gifted children with ADHD are more likely than gifted children without ADHD to indicate overall self‐esteem difficulties and lower levels of happiness and behavioral satisfaction (Foley‐Nicpon, Rickels, Assouline, & Richards, ).…”
Section: Key Conceptsmentioning
confidence: 99%
“…Because the current federal definition of giftedness does not provide specific guidelines for identifying gifted children (Foley-Nicpon, Rickels, Assouline, & Richards, 2012), there are varying standards researchers utilized to identify twice-exceptional children. Though not recommended practice, many schools have relied on and still do appear to rely on achievement and/or intelligence tests primarily or even solely to identify giftedness despite the recommendation for multiple assessments (Bracken & Brown, 2006;Sternberg, 2010;VanTassel-Baska, Feng, & de Brux, 2007;VanTassel-Baska, Feng, & Evans, 2007).…”
Section: Limitationsmentioning
confidence: 99%
“…Findings indicated that their characteristics contributed to their feelings of low-academic self-concept, depression or anxiety, and behavioral problems (Barber & Mueller, 2011;Baum, Cooper, & Neu, 2001;Cooper, Ness, & Smith, 2004;Dole, 2001;Kauder, 2009;Moon & Reis, 2004;Reis, Neu, & McGuire, 1997). Previous studies (e.g., Foley-Nicpon, Rickels, Assouline, & Richards, 2012;Strop & Goldman, 2002) specifically stated that 2e students typically exhibited social-emotional characteristics such as anger, fear of failure, fear of success, and low self-esteem. In general, 2e students manifest some psychological vulnerability to affective difficulties (Jackson, 1998;Neihart, 1998Neihart, , 1999Neihart, , 2002 and more emotional impairment than expected (Fletcher, Francis, Morris, & Lyon, 2005).…”
mentioning
confidence: 96%